Oral Health Related Quality of Life Among Completely Edentulous Patients - Elhddad, Abdelsalam I M; EL-Refadi, Roba I; Kablan, Rasha A (Libyan Journal of Dentistry, 2018)
Objectives: Age and tooth loss are expected to have a complex relationship with oral health-related quality of life so the purpose of this study was to assess the impact of tooth loss ( Edentulous) on oral health-related quality of life, using the short form of Oral Health Impact Profile (OHIP-14) among completely edentulous patients in one dental institution in Benghazi, Libya. Subjects and Methods: The study was performed at Faculty of Dentistry University of Benghazi, Libya. Patients attending dental clinics of prosthetic department. Those who needed dentures were interviewed using (OHIP-14), by one investigator. OHIP-14 assess perceived experiences of quality of life using 5 likert scale from 1 to 5 (1=never , 5=very often). The enrolment period was five months (January –May 2017). Socio demographic information were also collected. Only individuals who have been edentulous for the last three month were involved in the study. Data were analysed using descriptive statistics. Results: A total of 48 edentulous patients were recruited for this study, (56.2 %) of them were females. About 52.1% of participants were illiterate, while only (8.3%) have been graduate from university. About (75%) of participants have been often unable to function due to loss of their teeth. On the other hand (79.2%) of them ever or hardly ever got difficulty doing usual jobs because loss of their teeth. In our study we conclude that less than half of participants never or hardly ever got trouble with pronouncing any word because loss of their teeth. Conclusion: These findings suggest that teeth loss has significant impacts on quality of life. Further work is required to fully investigate these impacts and how we can intervene to improve the quality of life of these important group of patients.